MICROSCOPIC ROOT-CANAL RETREATMENT OF A MAXILLARY FIRST PREMOLAR - A CASE REPORT - Ruxandra Voinea Georgescu; Angela Abbas; Oana Andreea Diaconu; Mihaela Jana Țuculină (Romanian Society of Oral Rehabilitation, 2020)
The aim of this study is to emphasize the endodontic retreatment of the teeth to be restored prosthetically. Material and methods: At the radiological examination it was observed the existence of an incorrect endodontic treatment performed at the level of the tooth 14. Results: Chemo-mechanical treatment and root-canal filling were performed under a microscope. Conclusions: The number of endodontically treated teeth that require endodontic reintervention is high. From a subjective point of view, the skills of the dentist and his professional training greatly influence the quality and prognosis of an endodontic treatment.